PENGARUH KUALITAS PRODUK, BRAND IMAGE DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Konsumen Produk Kawa Punik di Desa Batu Dulang) - Andi Rusni (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This study is aimed at testing whether the Quality of the Product, the Brand Image and Trust in the Decision of the Purchase (Study cases on consumers Kawa Punik Product, on Batu Dulang Village, Batulanteh District, Sumbawa Regency). This research uses quantitative methods. The sample in this study amounted to 100 respondents obtained by nonprobability sampling method throuth an asiental sampling. The data obtained were processed using multiple linear analysis techniques using SPSS software. The results of the analysis in this study suggests that variables of product quality, the brand image and trust have a positive and significant impact on purchasing decision.